2000
DOI: 10.1111/j.1469-1795.2000.tb00238.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability and geographic structure of three subspecies of tigers (Panthera tigris) based on MHC class I variation

Abstract: Genetic variation at the major histocompatibility (MHC) class I loci was examined in captive and wild samples of three subspecies of tiger (Bengal, Panthera tigris tigris; Siberian, P. t. altaica; Sumatran, P. t. sumatrae) by Southern blot analysis using the domestic cat probe FLA 24. All captive populations showed at least moderate variability compared to other felids. Captive tigers were, on average, significantly more variable than wild tigers, but this was not consistent among subspecies. Significant geogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Cracraft et al (1998) and Hendrickson et al (2000) also described genetic variation distinguishing Sumatran tigers from other tiger subspecies. The relatively high genetic variability and phylogenetic distinctiveness of Sumatran tigers suggest a historically large effective population size followed by highly restricted gene flow between the island and other populations.…”
Section: Discussionmentioning
confidence: 99%
“…Cracraft et al (1998) and Hendrickson et al (2000) also described genetic variation distinguishing Sumatran tigers from other tiger subspecies. The relatively high genetic variability and phylogenetic distinctiveness of Sumatran tigers suggest a historically large effective population size followed by highly restricted gene flow between the island and other populations.…”
Section: Discussionmentioning
confidence: 99%
“…higher priority for breeding compared to generic zoo animals, ironically, doing so may decrease the overall genetic diversity of some species (Nowell and Jackson 1996;Hendrickson et al 2000;Uphyrkina and O'Brien 2003). If generic animals contain the genes of extinct populations, they should prove crucial for preserving the overall genetic diversity of the species.…”
Section: Implications For Ex Situ Lion Conservationmentioning
confidence: 97%
“…Comparative studies in the model and non-model organisms have shown that the high levels of genetic diversity observed at the MHC of vertebrate hosts are consistent with the hypothesis of pathogen-driven balancing selection through one of two mechanisms: Frequency-dependent selection and heterozygote advantage [ 18 , 25 , 26 , 27 ]. Consequently, high variations at the MHC loci reflect the level of fitness that can be exploited to genetically characterize different individuals in a population [ 18 , 28 , 29 , 30 , 31 , 32 ]. Thus, studying the variable sites of SLA molecules in as many suid breeds as possible is important to obtain crucial information on the SLA structure and the associations between SLA alleles and valuable traits.…”
Section: Introductionmentioning
confidence: 99%